Decision-Making Factors for Ulnar Nerve Transposition in Cubital Tunnel Surgery - DeGeorge, Brent R. (J Wrist Surg, 2019)
Background  We designed a survey to ascertain the current perspectives of hand surgeons on the evaluation and management of ulnar nerve instability at the elbow. The secondary aim was to assess the concordance of hand surgeons on definitions of the terms “subluxated” and “dislocated” for classification of ulnar nerve instability. Methods  A questionnaire, including demographic practice variables, cubital tunnel practice patterns, preoperative imaging and electrodiagnostic evaluation, and a series of standardized intraoperative photographs of ulnar nerve instability at the elbow were developed and distributed to the current American Society for Surgery of the Hand (ASSH) membership. Results  A total of 690 (26.8%) members completed the survey; 84.2% of respondents indicated that they evaluate for ulnar nerve instability preoperatively with clinical examination, whereas only 6.1% indicated they routinely obtained dynamic ultrasound. Respondents indicated that the factors most strongly influencing their decision to proceed with anterior transposition of the ulnar nerve were subluxation on physical examination (89.6%), history consistent with ulnar nerve subluxation (85.8%), and muscle atrophy (43.2%). On review of clinical photographs, respondents demonstrated varying degrees of agreement on the terms “subluxated” or “dislocated” and recommendations for ulnar nerve transposition at intermediate degrees of ulnar nerve instability. Conclusion  ASSH members routinely evaluate for ulnar nerve instability with history and clinical examination without uniform use of preoperative ultrasound, and nearly half of the time the decision to transpose the ulnar nerve is made intraoperatively. Definitions for the degree of ulnar nerve instability at the elbow are not uniformly agreed upon, and further development of a classification system may be warranted to standardize treatment.